RETHINKING THE AFRICAN ECONOMIC RECOVERY IN SUSTAINABLE DEVELOPMENT: THE CASE OF ENVIRONMENTAL PROJECTS - (:unkn) unknown (My University, 2016)
Several environmental projects are being developed in Africa with the goal of achieving sustainable development. Some of them include the mechanism for clean development, reducing emissions from deforestation and forest degradation, access to water facility or the forestry fund for the Congo Basin. As the demand for conciliating economic development and sustainable development increase, these projects have been conceived to contribute to the expansion of the economies in the countries in which they are established. Though the way to sustainability seems to be politically correct for an economic revival today, one has to ask if African economic revival can be realized through sustainable development considering the objectives of these environmental projects elaborated in Africa.
Keywords: African Research